2015
DOI: 10.9738/intsurg-d-13-00281.1
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Presenting Colon Cancer Is an Independent Predictor of Adverse Disease-Free Survival

Abstract: Twenty percent of colon cancers present as an emergency. However, the association between emergency presentation and disease-free survival (DFS) remains uncertain. Consecutive patients who underwent elective (CC) and emergent (eCC) resection for colon cancer were included in the analysis. Survival outcomes were compared between the 2 groups in univariate/multivariate analyses. A total of 439 patients underwent colonic resection for colon cancer during the interval 2000-2010; 97 (22.1%) presented as an emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 27 publications
3
40
0
1
Order By: Relevance
“…Unfortunately, this study lacks long-term follow-up, so there are no data regarding survival. However, the number of harvested lymph nodes and status of the surgical margins are considered good surrogate indicators of oncologic outcome, and on the basis of our series, we can therefore confirm the findings of the literature [6,8,21] that immediate resection itself should not affect long-term survival.…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 88%
“…Unfortunately, this study lacks long-term follow-up, so there are no data regarding survival. However, the number of harvested lymph nodes and status of the surgical margins are considered good surrogate indicators of oncologic outcome, and on the basis of our series, we can therefore confirm the findings of the literature [6,8,21] that immediate resection itself should not affect long-term survival.…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 88%
“…It is not possible to estimate directly from our data, how many emergency admissions would be “preventable” but as under 6% of private patients in the most affluent areas had emergency admission compared to 20% of public patients in the most deprived areas, a significant number of emergency admissions seems avoidable. The factors contributing to emergency admission in this study are similar to those associated with diagnostic and treatment delay . Almost all emergency admissions are likely to have been preceded by symptoms, although in a minority of cases the disease may have been occult prior to presentation .…”
Section: Discussionsupporting
confidence: 53%
“…We succeeded in estimating and testing a number of indirect effects and showed that emergency admission mediates a significant part of the influence of deprivation, private health insurance and marital status on survival. Emergency presentations pose complex clinical challenges, and are associated with advanced stage and co‐morbidity and a high rate of post‐operative complications . Some of the adverse impact of emergency admission may be mitigated by admission to a specialist centre which can deal with these complexities, and there may be a case for transfer to a specialist centre for definitive surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency CRC surgery is a clinical challenges (18,19) that associated with advanced stage and high morbidity and mortality (20,21,22) and a high postoperative complications rate (10,23). Our study revealed that emergency CRC surgery is more worse outcomes than elective CRC surgery group in all stages.…”
Section: Discussionmentioning
confidence: 54%